Comparative Analysis of Customer Satisfaction Using The Bandwidth Method Between Coaxial Cables and Fiber Optic Cables PT. Tbk Linknet - Yallah, Hasbi; Fathir, Akhmad; Darwis, Muhammad; Hendrowati, Retno (Teknik Informatika Universitas Pamulang, 2024)
This research aims to analyze the comparison of customer satisfaction between the use of coaxial cables and fiber optic cables in PT.LinkNet using the Bandwidth method. The Bandwidth method was used to evaluate network performance and the quality of service received by customers. Data was collected through customer satisfaction surveys covering aspects of service reliability, speed, stability and price. The analysis results indicate a notable difference in customer satisfaction levels between the two types of cable. Fiber optic cables received higher satisfaction ratings compared to coaxial cables.The results shows that the average satisfaction score for fiber optic cables was 4.7 out of 5, whereas coaxial cables received an average score of 3.9 out of 5. This difference is significant since evidenced by a p-value of less than 0.01, confirming that the higher satisfaction with fiber optic cables is not an outcome of random variation. These findings can provide input for PT Link Net in improving service quality and choosing the right technology to meet customer needs.